PENGARUH LINGKUNGAN SEKOLAH DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS XI SMA SWASTA TELADAN PEMATANGSIANTAR TAHUN AJARAN 2024/2025 - Novita Mayasari Purba; Wesly Nababan; Marthin Fransisco Manihuruk (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to determine whether ther is an influence of problem based learning and learning method on student learning achievement in citizenship education subject for class XI SMA Swasta Teladan Pematang Siantar academic year 2024/2025. The problem in this research is the influence of problem based learning dan learning method on student learning achievement in the citizenship education subject class XI P1 at SMA Negeri 1 Pematang Siantar for the 2024/2025 academic year.The population and sample in this study were all 48 students of class XI PMIPA. The instrument used are questionnaires and documentation. The quality of research instrument for questionnaires and student learning achievement is assessed through validity and reliability tests. All data from the three variables above were first tested whether they were normally distributed or not using a goodness of fit test or chi square test and it turned out that the three variables were normally distributed. The next step is testing the hypothesis by calculating the linear regression equation namely Y over X1 IS = 83,45+0,641 X1 meaning that the variable X1 is linier and Y and over X2 = 86,72 + 0,16 X2 means that the variable X2 is linier with Y and Y for X1 and X2 is = 4,4+ 0,25 X1 + 0,85 X2 means that variable X1 and X2 linier with Y The influence coefficient obtained is as follows : (1) The contribution coefficient of Y to X1 is 39,12% (2) The contribution coefficient of Y to X2 is 45,36% (3) The contribution coefficient of X1 over X2 is 45,36% (4) The contribution coefficient of Y to X1 and X2 is 43,28% Based on the hypothesis test, namely the significant influence test (t test) by rejecting H0 and accepting H1, we obtain : The influence of The School Environment on Student learning Achievement in Citizenship Education Subjects Class XI SMA Swasta Teladan Pematang Siantar T.A. 2024/2025 is “strong” (0,41). The influence of Learning method on Student learning Achievement in Citizenship Education Class XI SMA Swasta Teladan Pematang Siantar T.A. 2024/2025 is “ strong” (0,51). The influence of The School Environment and Learning method on Student learning Achievement in Citizenship Education Subjects XI SMA Swasta Teladan Pematang Siantar T.A. 2024/2025 is “strong” (0,51).